Changes in Kidney Function Do Not Differ between Healthy Adults Consuming Higher- Compared with Lower- or Normal-Protein Diets: A Systematic Review and Meta-Analysis. Issue 11 (1st November 2018) - Devries, Michaela C; Sithamparapillai, Arjun; Brimble, K Scott; Banfield, Laura; Morton, Robert W; Phillips, Stuart M
Abstract: Background: Higher-protein (HP) diets are advocated for several reasons, including mitigation of sarcopenia, but their effects on kidney function are unclear. Objective: This meta-analysis was conducted to determine the effect of HP intakes on kidney function in healthy adults. Methods: We conducted a systematic review and meta-analysis of trials comparing HP (≥1.5 g/kg body weight or ≥20% energy intake or ≥100 g protein/d) with normal- or lower-protein (NLP; ≥5% less energy intake from protein/d compared with HP group) intakes on kidney function. Medline and EMBASE databases were searched. Randomized controlled trials comparing the effects of HP with NLP (>4 d duration) intakes on glomerular filtration rate (GFR) in adults without kidney disease were included. Results: A total of 2144 abstracts were reviewed, with 40 articles selected for full-text review; 28 of these were analyzed and included data from 1358 participants. Data were analyzed using random-effects meta-analysis (RevMan 5; The Cochrane Collaboration), meta-regression (STATA; StataCorp), and dose-response analysis (Prism; GraphPad). Analyses were conducted using postintervention (post) GFR and the change in GFR from preintervention to post. The post-only comparison showed a trivial effect for GFR to be higher after HP intakes [standardized mean difference (SMD): 0.19; 95% CI: 0.07, 0.31; P = 0.002]. The change in GFR did not differ between interventions (SMD: 0.11; 95% CI: −0.05, 0.27; P = 0.16). There was a linear relation between protein intake and GFR in the post-only comparison ( r = 0.332, P = 0.03), but not between protein intake and the change in GFR ( r = 0.184, P = 0.33). The main limitation of the current analysis is the unclear risk of selection bias of the included trials. Conclusions: Postintervention GFR comparisons indicate that HP diets result in higher GFRs; however, when changes in GFR were compared, dietary protein had no effect. Our analysis indicates that HP intakes do not adversely influence kidney function on GFR in healthy adults.